Magnetic Z-type catalyst NiFe2O4 / BiFeO3 synthesized based on microwave hydrothermal method and having dual-response activity as well as preparation method and application of magnetic Z-type catalyst NiFe2O4 / BiFeO3

By combining microwave hydrothermal method and ultraviolet light-microwave synergistic effect on the catalyst NiFe2O4/BiFeO3, the problem of difficulty in removing antibiotics in water is solved, and an efficient, economical and environmentally friendly antibiotic degradation effect is achieved.

CN119733521AActive Publication Date: 2025-04-01LIAONING UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411856640.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove antibiotics in water, especially ciprofloxacin, and traditional treatment methods have problems of low degradation efficiency, high cost and secondary contamination.

Method used

The magnetic Z-type catalyst NiFe2O4/BiFeO3 with dual responsive activity synthesized based on microwave hydrothermal method is used to reduce electron-hole recombination through ultraviolet light-microwave synergistic action, thereby improving catalytic activity and achieving rapid degradation of antibiotics.

Benefits of technology

It achieves rapid and complete degradation of antibiotics in water, with high degradation efficiency, low cost and no secondary pollution, and is suitable for large-scale treatment of antibiotic wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192000150000041
    Figure BDA0005192000150000041
  • Figure BDA0005192000150000051
    Figure BDA0005192000150000051
  • Figure BDA0005192000150000052
    Figure BDA0005192000150000052
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic degradation, and particularly relates to a magnetic Z-type catalyst NiFe2O4 / BiFeO3 which is synthesized based on a microwave hydrothermal method and has double response activity as well as a preparation method and application of the magnetic Z-type catalyst NiFe2O4 / BiFeO3. According to the invention, the NiFe2O4 / BiFeO3 nanoparticle catalyst is obtained by adopting a microwave hydrothermal method, and antibiotics are degraded in combination with an ultraviolet light-microwave synergistic effect. As a new method for treating the antibiotic wastewater, the method has the advantages of high degradation efficiency, high speed, low cost, no secondary pollution and the like, is suitable for large-scale treatment of the antibiotic wastewater, and can quickly and thoroughly degrade the antibiotic wastewater in a short time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic degradation technology, and specifically relates to a magnetic Z-type catalyst NiFe with dual response activity synthesized based on a microwave hydrothermal method. 2 O 4 / BiFeO 3 Its preparation method and application in catalytic degradation of antibiotics in water under ultraviolet light-microwave. Background Art

[0002] Due to the progress of science and technology and pharmacology, antibiotic pollution is receiving more and more attention and has become an environmental problem that cannot be ignored. According to the different structures and mechanisms of action, common antibiotics can be divided into the following categories: quinolones, tetracyclines, sulfonamides, β-lactams and macrolides. Ciprofloxacin (CIP), as a widely used quinolone antibiotic, has been shown to alleviate bacterial infections in humans and animals. However, since it cannot be completely metabolized in the body, a large amount of ciprofloxacin will be discharged into the water system in the form of urine. Pollutants will inevitably accumulate in organisms along with water bodies and ecological cycles, leading to the emergence of diseases and antibiotic-resistant superbugs, and ultimately endangering ecosystems and biological organisms. Therefore, in an era when environmental and health considerations are crucial, eliminating antibiotics from water bodies is a major challenge. Given the resistance to degradation and high ecotoxicity of ciprofloxacin, traditional chemical and biological treatment methods are not sufficient for removing ciprofloxacin from water.

[0003] Nickel ferrite (NiFe 2 O 4 ) spinel shines among iron-based spinels due to its high reserves, low price, good stability, corrosion resistance, and environmental protection. In addition, its unique electronic configuration, adjustable valence state, and flexible structure give it great room for improvement. However, due to the NiFe 2 O 4 Due to its p-type semiconductor properties, its electron transfer is greatly restricted, resulting in low conductivity and insufficient utilization of active sites, which limits its application in catalysis.

[0004] Bismuth ferrite (BiFeO 3 ) has attracted much attention as a photocatalyst in solar catalysis due to its easily recyclable magnetic properties, suitable band gap value (2.2 eV), excellent chemical stability, and large polarization value, which is conducive to charge carrier separation. Despite the above characteristics, BiFeO has a limited application due to its fast electron-hole recombination rate. 3 Therefore, special attention should be paid to improving the photocatalytic efficiency of BiFeO 3The overall photocatalytic efficiency of the nanostructure. The most common way to improve the photocatalytic efficiency is to dope or form a composite material. Since doping can change the band structure and form a new composite material, it can effectively capture electrons to reduce electron-hole recombination. Summary of the invention

[0005] The purpose of the present invention is to provide a magnetic Z-type catalyst with dual-response activity synthesized based on a microwave hydrothermal method, which makes full use of microwave and ultraviolet light energy, reduces the recombination of electron-hole pairs, and thus improves the catalytic activity of the catalyst.

[0006] Another object of the present invention is to utilize the magnetic Z-type catalyst with dual-response activity to catalytically degrade antibiotics in water under ultraviolet light-microwave irradiation.

[0007] The technical solution adopted by the present invention is:

[0008] A magnetic Z-type catalyst with dual-response activity synthesized based on microwave hydrothermal method, wherein the Z-type catalyst is NiFe 2 O 4 / BiFeO 3 , made of NiFe 2 O 4 and BiFeO 3 Compound obtained.

[0009] Furthermore, the magnetic Z-type catalyst with dual-response activity synthesized by microwave hydrothermal method has a molar ratio of NiFe 2 O 4 :BiFeO 3 =1:3-3:1.

[0010] The method for preparing a magnetic Z-type catalyst with dual-response activity synthesized by microwave hydrothermal method comprises the following steps:

[0011] 1) Put Fe(NO 3 ) 3 9H 2 O and Bi(NO 3 ) 3 ·5H 2 O are dissolved in dilute nitric acid and stirred to mix. NaOH solution is dropped into the mixed solution to adjust the pH to 12. Stirring is continued. The obtained mixture is transferred to a PTFE reactor and placed on the turntable of a microwave hydrothermal synthesizer. The hydrothermal reaction is carried out at 1.5 MPa and 210°C for 30.0 min. After the reactor is cooled to room temperature, the obtained precipitate is washed to neutrality, filtered, dried, and ground to obtain red BiFeO 3 powder;

[0012] 2) Put Fe(NO3 ) 3 9H 2 O and Ni (NO 3 ) 2 6H 2 O were dissolved in deionized water, and Fe(NO 3 ) 3 9H 2 O solution was added dropwise to the Ni(NO 3 ) 2 6H 2 O solution and stirred to mix; NaOH solution was dropped into the mixed solution to adjust the pH to 12, and BiFeO 3 , continue stirring, transfer the obtained mixture into a PTFE reactor, place it on the turntable of a microwave hydrothermal synthesizer, and perform hydrothermal reaction at 1.5MPa and 180°C for 30.0min; after the reactor is cooled to room temperature, wash the obtained mixed precipitate to neutrality, filter, dry, and grind to obtain red NiFe 2 O 4 / BiFeO 3 powder.

[0013] A magnetic Z-type catalyst NiFe with dual-response activity synthesized by microwave hydrothermal method according to any one of the above 2 O 4 / BiFeO 3 Application of catalytic degradation of antibiotics in water under the synergistic effect of ultraviolet light and microwave.

[0014] Further, the above application method is as follows: adding a magnetic Z-type catalyst NiFe with dual-response activity synthesized by microwave hydrothermal method to a solution containing antibiotics 2 O 4 / BiFeO 3 , catalytic degradation under microwave and ultraviolet light.

[0015] Preferably, in the above application, the initial concentration of the antibiotic is 5.0-25.0 mg / L.

[0016] Preferably, in the above application, the magnetic Z-type catalyst NiFe with dual response activity synthesized by microwave hydrothermal method 2 O 4 / BiFeO 3 The dosage is 0.25-1.25g / L.

[0017] Preferably, in the above application, the microwave power is 100-600W, and the ultraviolet light power is 200W.

[0018] Preferably, in the above application, the catalytic degradation time is 2-10 min.

[0019] Preferably, in the above application, the antibiotic is ciprofloxacin.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention combines microwave catalysis with photocatalytic oxidation technology to design a magnetic Z-type catalyst NiFe with dual-response activity. 2 O 4 / BiFeO 3 , can make full use of ultraviolet light and microwave energy to reduce electrons (e - ) and holes (h + ) to improve the catalytic activity and achieve rapid and complete degradation of antibiotics in water.

[0022] 2. As a new method for treating antibiotic wastewater, the present invention has the advantages of high degradation efficiency, fast speed, low cost and no secondary pollution. It is suitable for large-scale treatment of antibiotic wastewater and can achieve rapid and thorough degradation of antibiotic wastewater in a short time. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 NiFe 2 O 4 Fourier transform infrared spectrum.

[0024] Figure 2 BiFeO 3 Fourier transform infrared spectrum.

[0025] Figure 3 NiFe 2 O 4 / BiFeO 3 Fourier transform infrared spectrum. DETAILED DESCRIPTION

[0026] Example 1

[0027] (I) Magnetic Z-type catalyst NiFe with dual-response activity 2 O 4 / BiFeO 3 The preparation method is as follows:

[0028] Synthesis of BiFeO by microwave hydrothermal method 3 Nanoparticles: Bi(NO 3 ) 3 ·5H 2 O and Fe(NO 3 ) 3 9H 2O is placed in 30.0 mL of dilute nitric acid and magnetically stirred at room temperature for 30 minutes to mix it thoroughly. NaOH solution is dropped into the mixed solution to adjust the pH to 12, and stirring is continued for 30.0 minutes. The resulting mixture is transferred to a PTFE reactor, placed on the turntable of a MW (2450 MHz) hydrothermal synthesizer, and subjected to a hydrothermal reaction at 1.5 MPa and 210°C for 30.0 minutes. After the reactor is cooled to room temperature, the reaction mixture is taken out and the resulting red precipitate is rinsed with deionized water until the pH is neutral. After filtering the mixture, it is placed in a vacuum oven at 80°C and dried for 12 hours. After drying, the powder is ground to obtain red BiFeO 3 powder.

[0029] Synthesis of NiFe by microwave hydrothermal method 2 O 4 Nanoparticles: 1mmol Ni(NO 3 ) 2 6H 2 O and 2mmol Fe(NO 3 ) 3 9H 2 O were dissolved in deionized water and fully dissolved. 3 ) 3 9H 2 O was added to a solution containing Ni(NO 3 ) 2 6H 2 O solution, and the mixed solution was magnetically stirred at room temperature for 30.0 min. NaOH solution was dropped into the mixed solution to adjust the pH to 12, and different molar ratios (NiFe 2 O 4 :BiFeO 3 =1:3-3:1) add BiFeO 3 , stirring continuously for 30.0 min. The resulting mixture was transferred to a PTFE reactor, placed on the turntable of a MW (2450 MHz) hydrothermal synthesizer, and subjected to a hydrothermal reaction at 1.5 MPa and 180 °C for 30.0 min. After the reactor was cooled to room temperature, the reaction mixture was taken out and the resulting red precipitate was rinsed with deionized water until the pH was neutral. The mixture was filtered and placed in a vacuum oven at 80 °C for 12 h. After drying, the powder was ground to obtain red NiFe 2 O 4 / BiFeO 3 Composite catalyst.

[0030] (II) Characterization of Catalyst

[0031] like Figure 1 As shown, in NiFe 2 O4 The FT-IR spectrum of -1 、422.91cm -1 The peaks correspond to the stretching vibrations of Fe-O and Ni-O. Therefore, the above results indicate that NiFe 2 O 4 The nanoparticles were successfully synthesized.

[0032] like Figure 2 As shown, in BiFeO 3 In the infrared spectrum, 455.12cm -1 The significant peak at 842.67 cm-1 belongs to the combination of Fe-O stretching vibration and O-Fe-O bending vibration. -1 The peak at belongs to the stretching vibration of Bi-O group. Therefore, the results can show that BiFeO 3 The nanoparticles were successfully synthesized.

[0033] like Figure 3 As shown, NiFe 2 O 4 / BiFeO 3 The characteristic peak is mainly located at 842.67cm -1 and 603.46cm -1 , belongs to NiFe 2 O 4 and BiFeO 3 The characteristic absorption peaks of NiFe can be observed within this range, and the position of the characteristic absorption peaks has no obvious change. Therefore, the above results fully prove that NiFe 2 O 4 / BiFeO 3 Nanocomposite photocatalysts.

[0034] (III) UV-visible absorption spectrum analysis of ciprofloxacin solution catalyzed by UV+MW

[0035] UV-microwave (UV+MW) catalytic degradation: 20.0 mL of ciprofloxacin solution (20 mg / L CIP) was measured and 0.5 g / L of catalyst powder (NiFe 2 O 4 / BiFeO 3 ) were mixed, irradiated with 200W ultraviolet light and 200W microwave for 10min, and the rotation speed was r = 200r / min. After the catalytic reaction was completed, the mixed solution was cooled to room temperature, centrifuged, filtered, and the ultraviolet spectrum of the supernatant was measured at 200-400nm. The absorbance at 278nm was used to calculate the degradation rate of ciprofloxacin. The results are shown in Table 1.

[0036] Degradation rate (%) = (C 0 -C) / C0 ×100%(where C 0 : concentration of stock solution; C: concentration of sample).

[0037] Table 1 NiFe under different conditions 2 O 4 / BiFeO 3 Effects on the degradation rate of ciprofloxacin

[0038]

[0039] As shown in Table 1, without adding a catalyst, the absorbance values ​​of the ciprofloxacin solution and the original solution under microwave-photocatalysis alone are almost the same, which indicates that the ciprofloxacin molecule is very stable under microwave-photocatalysis and the degree of degradation is minimal. When the catalyst is added, the absorbance value of ciprofloxacin decreases significantly. The data in the table also show that when MW and UV technology are used in combination, the degradation rate of ciprofloxacin is higher than when MW or UV is used alone, proving that MW and UV have a synergistic effect.

[0040] Example 2

[0041] (I) Effect of different molar ratios on the degradation rate of ciprofloxacin

[0042] Changing NiFe 2 O 4 / BiFeO 3 The molar ratio of the composition, microwave power 200W, UV power 200W, rotation speed r=200r / min, catalytic reaction 10min, ciprofloxacin 20.0mg / L, catalyst dosage 0.5g / L. The results are shown in Table 2.

[0043] Table 2 Effect of different molar ratios on the degradation rate of ciprofloxacin

[0044]

[0045] As shown in Table 2, in the UV-microwave catalytic system, the degradation rate of ciprofloxacin increases with the increase of NiFe 2 O 4 The increase in content shows a trend of first increasing and then decreasing. 2 O 4 :BiFeO 3 =2:1, the degradation rate of ciprofloxacin is the highest. In order to obtain a good degradation effect and reduce costs so as to be put into actual production, the present invention selects NiFe 2 O 4 :BiFeO 3 =2:1 is the optimal molar ratio.

[0046] (II) Effect of different microwave powers on the degradation rate of ciprofloxacin

[0047] Changing the microwave power, NiFe 2 O 4 :BiFeO 3 =2:1, UV light 200W, speed r=200r / min, catalytic reaction 10min, ciprofloxacin 20.0mg / L, catalyst dosage 0.5g / L. The results are shown in Table 3.

[0048] Table 3 Effect of different microwave powers on the degradation rate of ciprofloxacin

[0049]

[0050] As can be seen from Table 3, the degradation rate shows a trend of increasing first and then stabilizing with the increase of microwave (MW) power. Moreover, when the microwave power is 500 W, the degradation rate of ciprofloxacin has reached a maximum of 70.96%. The results show that higher microwave power can obtain high microwave irradiation intensity, which is conducive to the catalyst absorbing more microwave energy, so that more ciprofloxacin can be degraded.

[0051] (III) Effect of different initial concentrations on the degradation rate of ciprofloxacin

[0052] Changing the initial concentration of ciprofloxacin solution, NiFe 2 O 4 :BiFeO 3 =2:1, UV 200W, speed r=200r / min, microwave 500W, catalytic reaction 10min, catalyst dosage 0.5g / L. The results are shown in Table 4.

[0053] Table 4 Effect of different initial concentrations on the degradation rate of ciprofloxacin

[0054]

[0055] It can be seen from Table 4 that as the initial concentration of ciprofloxacin decreases, the degradation rate increases first and then stabilizes. 2 O 4 / BiFeO 3 The / UV+MW system had the best degradation effect, with a degradation rate of 76.23%.

[0056] (IV) Effect of different dosages on the degradation rate of ciprofloxacin

[0057] Changing the catalyst dosage, NiFe 2 O 4 :BiFeO 3=2:1, UV light 200W, speed r=200r / min, microwave 500W, catalytic reaction 10min, ciprofloxacin 10.0mg / L. The results are shown in Table 5.

[0058] Table 5 Effect of different dosages on the degradation rate of ciprofloxacin

[0059]

[0060] It can be seen from Table 5 that with the increase of catalyst dosage, the degradation rate of ciprofloxacin gradually increases. When the catalyst dosage is 1.25 g / L, NiFe 2 O 4 / BiFeO 3 The degradation effect of / UV+MW system was the best, with a degradation rate of 87.10%.

[0061] (V) Effect of different time on the degradation rate of ciprofloxacin

[0062] Changing composition technology and degradation time, NiFe 2 O 4 :BiFeO 3 =2:1, microwave power 500W, UV power 200W, speed r=200r / min, catalytic reaction 2-10min, ciprofloxacin 10.0mg / L, catalyst dosage 1.25g / L. The results are shown in Table 6.

[0063] Table 6 Effect of different UV-microwave composition technologies on the degradation rate of ciprofloxacin over time

[0064]

[0065] As can be seen from Table 6, as the irradiation time increases, the degradation rate increases. When MW and UV technology are used together, the degradation rate of ciprofloxacin is higher than when MW or UV is used alone, proving that MW and UV have a synergistic effect. When UV+MW is irradiated for 10 minutes, NiFe 2 O 4 / BiFeO 3 The degradation rate of the system was 83.50%. 2 O 4 / BiFeO 3 The degradation efficiency of the / UV+MW system is always higher.

[0066] (VI) Effect of different times of use on the degradation rate of ciprofloxacin

[0067] Molar ratio NiFe 2 O 4 :BiFeO 3=2:1, UV 200W, speed r=200r / min, microwave 500W, catalytic reaction 10min, ciprofloxacin 10.0mg / L, catalyst dosage 1.25g / L. The results are shown in Table 7.

[0068] Table 7 Effect of usage times on the degradation rate of ciprofloxacin

[0069]

[0070] It can be seen from Table 7 that the degradation rate of ciprofloxacin is relatively stable. This means that in five consecutive cycle tests, NiFe 2 O 4 / BiFeO 3 The UV+MW catalytic system showed good degradation activity. Therefore, the catalyst can be reused 5 times to remove pollutants in water, and the catalytic system still has good stability.

[0071] In the above embodiments, the antibiotic used is ciprofloxacin, but the antibiotic degraded in the present invention is not limited to ciprofloxacin. The method of the present invention is applicable to the degradation of any antibiotic, such as tetracycline, norfloxacin, sulfonamide, etc.

Claims

1. A magnetic Z-type catalyst with dual-response activity synthesized by microwave hydrothermal method, characterized in that: The Z-type catalyst is NiFe2O4 / BiFeO3, which is obtained by compounding NiFe2O4 and BiFeO3.

2. A magnetic Z-type catalyst with dual-response activity synthesized based on microwave hydrothermal method according to claim 1, characterized in that: In molar ratio, NiFe2O4:BiFeO3=1:3-3:

1.

3. The method for preparing a magnetic Z-type catalyst with dual-response activity synthesized by microwave hydrothermal method according to claim 2, characterized in that: The steps include: 1) Dissolve Fe(NO3)3·9H2O and Bi(NO3)3·5H2O in dilute nitric acid, stir to mix, drop NaOH solution into the mixed solution to adjust pH=12, continue stirring, transfer the obtained mixture into a PTFE reactor, place it on the turntable of a microwave hydrothermal synthesizer, and perform hydrothermal reaction at 1.5MPa and 210°C for 30.0min; after the reactor is cooled to room temperature, wash the obtained precipitate to neutrality, filter, dry and grind to obtain red BiFeO3 powder; 2) Dissolve Fe(NO3)3·9H2O and Ni(NO3)2·6H2O in deionized water respectively, add Fe(NO3)3·9H2O solution dropwise into Ni(NO3)2·6H2O solution, and stir to mix; NaOH solution was dropped into the mixed solution to adjust the pH to 12, BiFeO3 was added in a molar ratio, and stirring was continued. The obtained mixture was transferred to a PTFE reactor, placed on the turntable of a microwave hydrothermal synthesizer, and a hydrothermal reaction was carried out at 1.5 MPa and 180°C for 30.0 min. After the reactor was cooled to room temperature, the obtained mixed precipitate was washed to neutrality, filtered, dried, and ground to obtain red NiFe2O4 / BiFeO3 powder.

4. Application of the magnetic Z-type catalyst NiFe2O4 / BiFeO3 with dual-response activity synthesized by microwave hydrothermal method as described in claim 1 or 2 to catalytic degradation of antibiotics in water under the synergistic effect of ultraviolet light and microwave.

5. The use according to claim 4, characterized in that: The method is as follows: a magnetic Z-type catalyst NiFe2O4 / BiFeO3 with dual-response activity synthesized by microwave hydrothermal method is added to a solution containing antibiotics, and catalytic degradation is carried out under microwave and ultraviolet light.

6. The use according to claim 5, characterized in that: The initial concentration of the antibiotic is 5.0-25.0 mg / L.

7. The use according to claim 6, characterized in that: The dosage of the magnetic Z-type catalyst NiFe2O4 / BiFeO3 with dual-response activity synthesized based on the microwave hydrothermal method is 0.25-1.25 g / L.

8. The use according to claim 5, characterized in that: The microwave power is 100-600W, and the ultraviolet light power is 200W.

9. The use according to claim 8, characterized in that: The catalytic degradation time is 2-10 minutes.

10. The use according to claim 4, characterized in that: The antibiotic is ciprofloxacin.

Citation Information

Patent Citations

  • Visible-light responsive magnetic photocatalytic material and preparation method thereof

    CN103877985A

  • Rapid synthesis method of single-phase bismuth ferrite visible-light-driven photocatalyst

    CN105772003A

  • Ferromagnetic / anti-ferromagnetic heterojunction with exchange bias effect and preparation method thereof

    CN110228822A

  • Nano nickel ferrite / zinc titanate modified microporous silicon oxide as well as preparation method and application thereof

    CN113786825A

  • Preparation method and application of magnetic nano-iron particle coated graphene composite material

    CN117046482A